A User-based design process for web database: Case study melaka k-economy incubator database - Mat Jusoh, Normal; Ismail, Ishak; Mohd. Noah, Sharul Azman (2002)
The paper proposes a novel concept in designing a data integrated web database which incorporates three kernels which point towards database cells related to the development of Melaka K-Economy Incubator catalysed by Cottage Industries, Investors' Trend and Intellectual Properties resulting from the research work from local universities and research institutes. The study takes into consideration many factors which facilitate improvement on human computer interaction (HCI) with regards to efficiency and QOS as perceived by the user. Research by V.A.J. Maller 1 has indicated that failure of systems analyst and designer is a dominant factor in deciding efficiency and QOS of any data integrated web database. In this study certain features have been added to design of the database to ensure that the negative effects of systems analyst and designer failure is minimised. The user-based design process is an extension of the work of Eillen G. Abel et al 2 who designed the web interface and whose idea is currently further developed to design a web database where design decisions emanates from the user rather than from the designer view point throughout the process.